Critical Race Theory: Opportunities for Application in Social Work Practice and Policy. Issue 4 (October 2014) - Kolivoski, Karen M.; Weaver, Addie; Constance-Huggins, Monique
Critical race theory (CRT) provides a framework for examining power structures that maintain racial inequities and developing strategies for action and change. Though social work acknowledges racial disparities and the role of racism when identifying and attempting to ameliorate social problems, the profession has not fully incorporated CRT. This article introduces CRT, articulates its alignment with social work's professional mission and values, describes its central tenets, and applies the tenets to racial disparities within three areas of practice particularly relevant for social work: child welfare system involvement, receipt of public assistance, and access to mental health treatment. CRT's broader implications for social work practice are identified and discussed.